On the social inappropriateness of discrimination - Abigail Barr; Tom Lane; Daniele Nosenzo (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2017)
We experimentally investigate the relationship between discriminatory behaviour and the perceived social inappropriateness of discrimination. We test the framework of Akerlof and Kranton (2000, 2005), which suggests discrimination will be stronger when social norms favour it. Our results support this prediction. Using a Krupka-Weber social norm elicitation task, we find participants perceive it to be less socially inappropriate to discriminate on the basis of social identities artificially induced, using a trivial minimal group technique, than on the basis of nationality. Correspondingly, we find that participants discriminate more in the artificial identity setting. Our results suggest norms and the preference to comply with them affect discriminatory decisions and that the social inappropriateness of discrimination moderates discriminatory behaviour.
Keywords: C71; C92; D03; 330; discrimination; social norms; Krupka-Weber method; allocator game